Pengaruh Tax Avoidance Dan Beban Pajak Tangguhan Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024) - Raden Muhamad Arifin Ilham; Mahwiyah Mahwiyah (Journal of Innovative and Creativity, 2025)
This study aims to examine the effect of Tax Avoidance and Deferred Tax Expenses on Earnings Management. The object of this study used 35 industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2024 period that had met the criteria and completeness of the data. The data collection technique used the Purposive Sampling method. The data used in this study are secondary data. Using the financial statements of industrial sector manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2024 period, the research method used linear regression analysis. The results of the study showed that Tax Avoidance had a significant positive effect on Earnings Management and Deferred Tax Expenses had a significant negative effect on Earnings Management